Measurements of total reactive nitrogen during the Airborne Arctic Stratospheric Expedition - Kawa, S. R.; Fahey, D. W.; Anderson, L. C.; Loewenstein, M.; Chan, K. R. (1990)
Composite distributions of measured total reactive nitrogen NO(y), from the NASA ER-2 during the Airborne Arctic Stratospheric Expedition are presented. The observed features of these distributions are discussed in terms of the controlling dynamical, chemical and microphysical processes. In the latitudinal profile from 58 deg N to within about 4 deg poleward of the polar vortex boundary, NO(y) conforms closely to predictions of NO(y) based on N2O measurements. Poleward of 5 deg of latitude within the boundary, the average NO(y) decreases sharply and is significantly lower than that predicted from N2O. This feature is consistent with loss of NO(y) through sedimentation of particles containing NO(y) in polar stratospheric clouds.